Benefaction from carbonation of flue gas CO2 as coal mining filling - Tosun, Yıldırım İsmail (Scientific Research : www.scirp.org, 2014)
CO2 capturing, transport and sequestration by pressurized water dissolution and reacting by nat- ural alkali lime and magnesia in coal fly ash or other sources become an industrial advantageous sequestration option resulting in green waste solutions or solid fines. Mg and Ca containing min- erals are reacting with CO2 to form carbonates. Various types of fly ash materials may react with CO2 to form carbonate regarding ash composition and reaction parameters. Mineral sequestration of CO2 will also allow using the products in cement industry or as cement material in constructions with low cost. This paper discussed progress on coal mining filling by carbonation method using coal fly ash of Soma, Yatagan, Afşin Elbistan Power Stations. Other filler materials containing coal mine waste shale, fly ashes and foam concrete, and additives were searched for pretreatment me- thods to enhance cement reactivity; and in analyzing the structural changes to identify reaction paths and potential barriers.
Keywords: Carbon Sequestration; Coal Fly Ash Utilization; Mineral Carbonation; Mineralization; Fly Ash